Pengaruh Media Powtoon terhadap Keterampilan Menulis Teks Deskripsi pada Siswa Kelas VII SMP Negeri 1 Cijaku Kabupaten Lebak - Althafunisa, Rizka (Jurnal Artikula, 2025)
The Influence of Powtoon Media on Descriptive Text Writing Skills in Grade VII Students of SMP Negeri 1 Cijaku, Lebak Regency. Thesis. Indonesian and Regional Language and Literature Education Study Program. Faculty of Teacher Training and Education. Mathla'ul Anwar University. Banten. 2024.This study aims to determine the influence of Powtoon Media on the skill of writing description texts in grade VII students of SMP Negeri 1 Cijaku, Lebak Regency. This research was conducted based on the problem of low descriptive text writing skills in junior high school students which is characterized by students having difficulty in doing problems that are different from those exemplified by their teachers. The method in this study uses a quantitative method. The population and sample of this study are grade VII students of SMP Negeri 1 Cijaku as many as 2 classes that are randomly selected or Random Sampling. The instrument used in this study is a test of writing skills in descriptive text. The test used is in the form of a question type test. Based on the results of data analysis, the results of this study were concluded: there was a difference in the influence of description text writing skills of students who learned using Powtoon media and students who learned using Canva media. The skills of writing description texts of students who learned Powtoon media were better than those of students who learned using canva media. This can be seen from the results of the hypothesis test, namely by using an independent samples test obtained from a value of 0.21 <0.05, which means that the variance between groups is not the same. So it can be concluded that there is a significant difference in the increase in the influence of Powtoon media on the writing skills of junior high school students' description texts